2022
DOI: 10.1186/s12903-022-02417-6
|View full text |Cite
|
Sign up to set email alerts
|

Launching an innovative educational model addressing substance use disorders and dental pain management (Project ECHO® in dentistry)

Abstract: Background: Uninformed opioid prescribing by dentists has contributed to the current opioid crisis. This report describes the development and implementation of an innovative, interactive, multidisciplinary, and participant-centric telementoring program "Pain Management and Substance Use Disorders Dental ECHO (Extension for Community Health Care Outcomes)". We disseminated information to dentists about appropriate opioid prescribing practices and engaged them with a focus on pain management and substance use di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Future research would benefit from exploration of dental practice styles in these regions. Continuing education for dental providers may be another possible mechanism through which to address inappropriate prescribing of drugs with safety risks 38 . It is important to note that some trends, including the observed 2016 increase in sedative fills, were driven by a small number of dentists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research would benefit from exploration of dental practice styles in these regions. Continuing education for dental providers may be another possible mechanism through which to address inappropriate prescribing of drugs with safety risks 38 . It is important to note that some trends, including the observed 2016 increase in sedative fills, were driven by a small number of dentists.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing education for dental providers may be another possible mechanism through which to address inappropriate prescribing of drugs with safety risks. 38 It is important to note that some trends, including the observed 2016 increase in sedative fills, were driven by a small number of dentists. These findings are consistent with a recent study which found that 5% of dentists were responsible for almost half of opioid prescriptions to adults in 2019.…”
Section: Post-hoc Analysesmentioning
confidence: 99%